Monkeys - Canizares, Susan, 1960-; Chanko, Pamela, 1968- (New York : Scholastic, 1998)
Photographs and simple text explore the daily activities of monkeys in the Amazon rain forest.
1.0
K-3
Keywords: Monkeys -- Juvenile literature; Monkeys; Monkeys